Impact : great leadership changes everything - Irwin, Tim, 1949- (2014)
"For more than 25 years, organizational psychologist and management consultant Dr. Tim Irwin has worked with thousands of leaders in well-known global companies. He knows most leaders work for recognition and advancement and they want more challenge and responsibility. He's also found this to be true: Most of us want to make a positive difference through our work and to have our lives count for something more than simply making a living. We want to make an impact. Yet when we look around our organizations, we don't see many leaders who have real impact. We see them just managing the daily rat race. Somewhere along the line, many began working for money instead of for meaning, for status instead of for a lasting legacy. In Impact, Irwin identifies the principles and beliefs that lead to great leadership-ways in which you can grow and thrive and be trusted by others. Learn how to be the kind of leader that motivates others in meaningful work and great accomplishments and what you can do to stay on track so you avoid a path of personal destruction so many leaders go down today. Accessible, humorous, and engaging, Irwin's latest book shows you how to live the vision you began your career with and then finish strong for a lasting impact, the hope of every great leader"--
Includes bibliographical references and index
Keywords: Leadership